PENGARUH MODEL BODILY KINESTHETIC INTELLIGENCE TERHADAP KETERAMPILAN GERAK TARI PADA SISWA KELAS V SDN 174552 TAMBUNAN - Imel Fitaloca Tambunan; Putra Afriadi; Apiek Gandamana; Winara; Sri Mustika Aulia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
ABSTRACT This study aims to determine the effect of the Bodily Kinesthetic Intelligence learning model on the dance movement skills of Class V students at SDN 174552 Tambunan. This research employed a Quasi-Experimental Design using a Non-equivalent Control Group Design with pretest and posttest administration on two groups: an experimental group and a control group. The subjects were 44 fifth-grade students (22 experimental, 22 control) at SDN 174552 Tambunan, Balige District, Toba Regency, North Sumatra. Data collection instruments included dance movement skill observation sheets covering aspects of wiraga, wirama, wirasa, and harmony, along with a Zapin Melayu dance assessment rubric validated through expert judgment. Data analysis comprised normality tests (Shapiro-Wilk), homogeneity tests (Levene), independent sample t-tests, N-Gain analysis, and effect size (Cohen’s d). The results showed a significant posttest difference: the experimental group achieved a mean of 70.341 compared to 47.159 for the control group (t = 12.626, p < 0.001). The N-Gain analysis yielded a mean of 0.504 (moderate category) for the experimental group versus 0.083 (low category) for the control group. The Cohen’s d value of 3.807 indicates a large practical effect. It is concluded that the Bodily Kinesthetic Intelligence model has a significant positive effect on dance movement skills of Class V students at SDN 174552 Tambunan.